Hydroxyapatite nanowire coated with metal ion-rich amorphous layer and preparation method thereof
By dispersing hydroxyapatite nanowires in the buffer solution and adding metal salts to form a metal ion-rich amorphous layer, the problems of difficult preparation and morphology regulation in the prior art are solved, and the efficient preparation of hydroxyapatite nanowires with excellent mechanical properties and thermal stability are achieved.
Patent Information
- Application Number
- CN202411717193.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-27
AI Technical Summary
The prior art is difficult to effectively prepare and morphologically regulate hydroxyapatite nanowires coated with metal ion-rich amorphous layers, especially in multi-stage structures that simulate tooth enamel.
By dispersing the hydroxyapatite nanowires in a buffer solution and adding soluble metal salts to the reaction, a hydroxyapatite nanowires coated with a metal ion-rich amorphous layer is formed. The method includes stirring and ultrasonic dispersion at room temperature followed by washing, centrifugation and freeze-drying.
The rapid synthesis of hydroxyapatite nanowires with high aspect ratios at room temperature is achieved. The outer amorphous layer is formed by ion replacement of metal ions and hydroxyapatite, enhancing the mechanical properties and thermal stability of the nanowires.
Smart Images

Figure CN119591065A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nano material preparation, and in particular to hydroxyapatite nanowires coated with a metal ion-rich amorphous layer and a preparation method thereof. Background Art
[0002] Tooth enamel is the hardest material in the human body, composed of 96 wt% hydroxyapatite and 4 wt% hydrated protein. Tooth enamel covers the surface of teeth and is several millimeters thick. It is known for its high stiffness, hardness and viscoelasticity, and has excellent toughness to resist vibration and impact during chewing. It combines multiple contradictory mechanical properties such as high hardness, high elasticity, high strength and high toughness, and can protect teeth from external physical and chemical damage. Tooth enamel is a typical multi-level structure, mainly composed of enamel prisms and enamel interstitium. The smallest structural unit of the enamel prism is a single hydroxyapatite nanocrystal, which grows along the c-axis to form linear hydroxyapatite nanocrystals. Between the enamel prisms of tooth enamel, there is a protein-rich organic layer called the "sheath", and the hydroxyapatite crystals are "bound" together under the action of the organic matrix. Further research found that there is an inorganic amorphous interstitial layer between hydroxyapatite nanowires. This interface characterization shows that there is a strong chemical bond between the amorphous layer and the nanowires, which enhances the interface connectivity. This multi-level micro-nanostructure is the key to the excellent mechanical properties of enamel.
[0003] The preparation of artificial enamel or enamel repair materials by simulating the structure of enamel has great application potential in the biomedical field. At present, it is still difficult to achieve the preparation and morphology control of inorganic amorphous nanomaterials. Introducing an amorphous interstitial layer that plays a key role in mechanical properties to imitate the multi-level structure of enamel is still a huge challenge. Patent publication number CN117246991A discloses a fluoroapatite nanorod with a magnesium amorphous layer on the surface and a preparation method thereof. The method dissolves a soluble salt in water and drips it so that when the nanoclusters are randomly attached and oriented and crystallized, the magnesium ions are squeezed to the edge of the nanorods to form fluoroapatite nanorods coated with a magnesium amorphous layer. Professor Guo Lin's research group at the Beijing University of Aeronautics and Astronautics has developed a method for coating hydroxyapatite nanowires with an amorphous layer of zirconium oxide. Based on the controllable growth theory of ice crystals, the nanowires use the crystal / amorphous composite nanowires as the basic structural unit and use a self-designed device to achieve the directed assembly of amorphous / crystal composite nanowires and polyvinyl alcohol polymers on a macro scale, preparing HA-based composite materials with enamel-like structures and preparing enamel-like materials. The above methods are relatively complex, greatly affected by environmental factors, and have low controllability. Summary of the invention
[0004] In view of the technical problems existing in the background technology, the present application provides a hydroxyapatite nanowire coated with a metal ion-rich amorphous layer and a preparation method thereof, aiming to solve the technical problem that the preparation and morphology control of hydroxyapatite nanowire coated with a metal ion-rich amorphous layer are still relatively difficult.
[0005] In a first aspect, an embodiment of the present application provides a hydroxyapatite nanowire coated with a metal ion-rich amorphous layer, comprising a hydroxyapatite nanowire and a metal ion-rich amorphous layer coated on the surface thereof, wherein the aspect ratio of the hydroxyapatite nanowire is 500~10000, and the ratio of the diameter of the hydroxyapatite nanowire to the thickness of the metal ion-rich amorphous layer is (5~50):1.
[0006] Preferably, the diameter of the hydroxyapatite nanowire is 10-100 nm, and the length is 100-500 μm; the thickness of the metal ion-rich amorphous layer is 1-5 nm.
[0007] Preferably, the metal ion includes one of iron, aluminum, copper, manganese and zinc.
[0008] In a second aspect, the present invention provides a method for preparing hydroxyapatite nanowires coated with a metal ion-rich amorphous layer, comprising the following steps: S1, dispersing hydroxyapatite nanowires in a buffer solution to obtain a hydroxyapatite nanowire suspension solution; S2. Adding a soluble metal salt to the hydroxyapatite nanowire suspension solution, stirring the suspension solution for reaction, and washing, centrifuging, and freeze-drying the suspension solution after the reaction is completed to obtain hydroxyapatite nanowires coated with a metal ion-rich amorphous layer.
[0009] Preferably, the buffer solution is an ammonium formate-formic acid buffer solution or a glycine-sodium hydroxide buffer solution, and the pH of the buffer solution is 5.0-9.0.
[0010] Preferably, the concentration of hydroxyapatite nanowires in the hydroxyapatite nanowire suspension solution is 2-5 g / L.
[0011] Preferably, the dispersing step in step S1 comprises placing the hydroxyapatite nanowires in a buffer solution, stirring at room temperature for 12 to 24 hours, and then performing ultrasonic dispersion at a power of 600 to 800 W for 30 to 60 minutes.
[0012] Preferably, the metal ion concentration in step S2 is 0.0001-0.025 mol / L, and the metal ion and Ca in hydroxyapatite 2+ The molar ratio is 1:(2~10).
[0013] Preferably, the stirring conditions in step S2 are: stirring at room temperature for 3 to 24 hours, and the stirring speed is 400 to 800 rpm.
[0014] In a third aspect, an embodiment of the present application provides a tooth enamel repair material prepared from hydroxyapatite nanowires coated with a metal ion-rich amorphous layer.
[0015] Different from the existing technical solutions, the beneficial effects of this application include: 1. This application studies the unique structure of natural tooth enamel and coats the outer layer of hydroxyapatite nanowires with an amorphous layer containing rich iron, aluminum, copper, manganese, and zinc metal ions, respectively, to simulate the multi-level structure of hydroxyapatite nanowires in natural tooth enamel, so that it has some excellent properties of hydroxyapatite nanowires given by metal ions, such as good thermal stability and wear resistance. The nanowires can be further processed to obtain artificial tooth enamel, tooth enamel repair materials, etc., which can be used for basic research and clinical applications in related fields such as biomaterials and tissue engineering.
[0016] 2. The present application discloses a method for preparing a hydroxyapatite nanowire coated with a metal ion-rich amorphous layer, which can quickly synthesize a hydroxyapatite nanowire coated with a metal ion-rich amorphous layer at room temperature. The hydroxyapatite nanowire has a high aspect ratio, and the outer amorphous layer is formed by metal ions and hydroxyl groups, Ca 2+ Ion replacement occurs around the nanowires. Since there are strong chemical bonds between the amorphous phase and the nanowires, the material is strengthened and toughened, and the mechanical properties of the hydroxyapatite nanowires can be improved. At the same time, due to a small amount of ion exchange between the metal ions and the calcium ions in the hydroxyapatite nanowires, an amorphous layer is generated around the nanowires. This amorphous layer rich in metal ions increases the stability of the hydroxyapatite nanowires in high temperature environments, making it have some excellent properties given to hydroxyapatite nanowires by metal ions, such as improved thermal stability and wear resistance.
[0017] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0019] Figure 1 This is the TEM image of Al-HAP nanowires in Example 1.
[0020] Figure 2 The XRD patterns of Al-HAP nanowires and pure hydroxyapatite nanowires in Example 1.
[0021] Figure 3 The XPS graphs of Al-HAP nanowires and pure hydroxyapatite nanowires in Example 1.
[0022] Figure 4 This is a SEM image of the Al-HAP nanowires in Example 1 at a magnification of 10,000 times.
[0023] Figure 5 This is the TEM image of Mn-HAP nanowires in Example 2.
[0024] Figure 6 These are the XRD test patterns of Mn-HAP, HAP and Mn-HAP-900℃ nanowires in Example 2.
[0025] Figure 7 This is the XPS test graph of Mn-HAP and HAP nanowires in Example 2.
[0026] Figure 8 This is a SEM image of Mn-HAP in Example 2 at a magnification of 10,000 times.
[0027] Fig. 9 This is the TEM image of Fe-HAP nanowires in Example 3.
[0028] Fig.10 These are the XRD test patterns of Fe-HAP, HAP and Fe-HAP-900℃ nanowires in Example 3.
[0029] Fig.11 This is the XPS test graph of Fe-HAP and HAP nanowires in Example 3.
[0030] Fig.12 This is a SEM image of Fe-HAP in Example 3 at a magnification of 10,000 times.
[0031] Fig.13 This is the thermogravimetric analysis diagram of Al-HAP in Example 1.
[0032] Fig.14 This is the TEM image of Mn-HAP nanowires in Comparative Example 1.
[0033] Fig.15 This is the TEM image of Mn-HAP nanowires in Comparative Example 2.
[0034] Fig.16 This is the TEM image of Mn-HAP nanowires in Comparative Example 3. DETAILED DESCRIPTION
[0035] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0036] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0037] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0038] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0039] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0040] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).
[0041] The preparation of artificial enamel or enamel repair materials that simulate the structure of enamel has great application potential in the biomedical field. At present, it is still difficult to achieve the preparation and morphology control of inorganic amorphous nanomaterials, and it is still a huge challenge to introduce an amorphous interstitial layer that plays a key role in mechanical properties to imitate the multi-level structure of enamel.
[0042] In order to solve the technical problem that the preparation and morphology control of inorganic amorphous nanomaterials are still relatively difficult, the present application provides a hydroxyapatite nanowire coated with a metal ion-rich amorphous layer and a preparation method thereof, wherein, by learning the unique structure of natural enamel, an unreported metal ion-rich amorphous layer is introduced into the outer layer of the hydroxyapatite nanowire to construct a new amorphous layer-coated hydroxyapatite nanowire. The nanowire can be further processed to obtain artificial enamel, enamel repair materials, etc., which can be used for basic research and clinical applications in related fields such as biomaterials and tissue engineering.
[0043] In a first aspect, an embodiment of the present application provides a hydroxyapatite nanowire coated with a metal ion-rich amorphous layer, comprising a hydroxyapatite nanowire and a metal ion-rich amorphous layer coated on the surface thereof, wherein the hydroxyapatite nanowire has a diameter of 10 to 100 nm and a length of 100 to 500 μm, and the metal ion-rich amorphous layer has a thickness of 1 to 5 nm.
[0044] Preferably, the metal ion includes one of iron, aluminum, copper, manganese and zinc.
[0045] In a second aspect, the present invention provides a method for preparing hydroxyapatite nanowires coated with a metal ion-rich amorphous layer, comprising the following steps: S1, dispersing hydroxyapatite nanowires in a buffer solution to obtain a hydroxyapatite nanowire suspension solution; S2. Adding a soluble metal salt to the hydroxyapatite nanowire suspension solution, stirring the suspension solution for reaction, and washing, centrifuging, and freeze-drying the suspension solution after the reaction is completed to obtain hydroxyapatite nanowires coated with a metal ion-rich amorphous layer.
[0046] Preferably, the buffer solution is an ammonium formate-formic acid buffer solution or a glycine-sodium hydroxide buffer solution, and the pH of the buffer solution is 5.0-9.0.
[0047] In the technical solution of the embodiment of the present application, ammonium formate-formic acid or glycine-sodium hydroxide is used as the buffer solution for adjusting the pH, which can avoid excessive pH changes during the reaction and facilitate stabilizing the pH within the required range.
[0048] Preferably, the concentration of hydroxyapatite nanowires in the hydroxyapatite nanowire suspension solution is 2-5 g / L.
[0049] Preferably, the dispersing step in step S1 comprises placing the hydroxyapatite nanowires in a buffer solution, stirring at room temperature for 12 to 24 hours, and then performing ultrasonic dispersion at a power of 600 to 800 W for 30 to 60 minutes.
[0050] Preferably, the metal ion concentration in step S2 is 0.0001-0.025 mol / L.
[0051] Preferably, the metal ion is Ca in hydroxyapatite 2+ The molar ratio is 1:(2~10).
[0052] Preferably, the stirring condition in step S2 is: stirring at room temperature for 3 to 24 hours.
[0053] In a third aspect, an embodiment of the present application provides a tooth enamel repair material prepared from hydroxyapatite nanowires coated with a metal ion-rich amorphous layer.
[0054] In the technical solution of the embodiment of the present application, hydroxyapatite nanowires coated with a metal ion-rich amorphous layer are used through ice templates, self-assembly and other methods to achieve the preparation of multi-scale ordered structure materials based on hydroxyapatite nanowires. Due to the coating of the metal ion-rich amorphous layer, the material has better mechanical properties, and the ordered structure material can be used in hard tissue repair, such as enamel and other biomedical fields, and has good application prospects.
[0055] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.
[0056] 1. Preparation method Example 1 Preparation method of hydroxyapatite nanowires coated with aluminum-rich amorphous layer: (1) 0.125 g of HAP (hydroxyapatite) nanowires were placed in an ammonium formate-formic acid buffer solution with a pH of 5.0, stirred at room temperature overnight, and ultrasonically dispersed at a power of 600 W for 30 min to obtain a 2.5 g / L milky white suspension solution; the hydroxyapatite nanowires used were hydroxyapatite nanowires with a diameter mainly dispersed in the range of 10-50 nm and a length of about 100 µm.
[0057] The preparation method of hydroxyapatite nanowires is as follows: hydroxyapatite nanowires are prepared by a solvothermal method, firstly, sodium hydroxide, calcium chloride, sodium dihydrogen phosphate solution and a mixed solution of oleic acid, water and anhydrous ethanol are prepared respectively; then, the sodium hydroxide solution is added to the oleic acid mixed solution by a peristaltic pump, and the mixture is reacted at a speed of 700-1100 rpm for half an hour, and then the calcium chloride solution and the sodium dihydrogen phosphate solution are added respectively, with an addition interval of half an hour; finally, the mixture is poured into a polytetrafluoroethylene container, and the container is placed in a reactor and reacted at 180°C for 24 hours to prepare the nanowires.
[0058] (2) Add 0.042 g of Al2(SO4)3·18H2O to the solution in step (1) and stir at room temperature for 3 h; the ratio of aluminum ions in the system to calcium ions in hydroxyapatite is 1:10.
[0059] (3) After the reaction is complete, centrifuge with ultrapure water for 3 times to obtain a white precipitate product. Put the white precipitate into a refrigerator for more than 6 hours and freeze-dry it in a freeze dryer for 24 hours to obtain Al-HAP nanowires.
[0060] Example 2 Preparation method of hydroxyapatite nanowires coated with a manganese-rich amorphous layer: (1) 0.125 g of HAP nanowires were placed in a glycine-sodium hydroxide buffer solution with a pH of 9, stirred at room temperature overnight, and ultrasonically dispersed at a power of 600 W for 30 min to obtain a 2.5 g / L milky white suspension solution; the hydroxyapatite nanowires used were hydroxyapatite nanowires with a diameter mainly dispersed in the range of 10-50 nm and a length of about 100 µm.
[0061] The preparation method of hydroxyapatite nanowires is as follows: hydroxyapatite nanowires are prepared by a solvothermal method, firstly, sodium hydroxide, calcium chloride, sodium dihydrogen phosphate solution and a mixed solution of oleic acid, water and anhydrous ethanol are prepared respectively; then, the sodium hydroxide solution is added to the oleic acid mixed solution by a peristaltic pump, and the mixture is reacted at a speed of 700-1100 rpm for half an hour, and then the calcium chloride solution and the sodium dihydrogen phosphate solution are added respectively, with an addition interval of half an hour; finally, the mixture is poured into a polytetrafluoroethylene container, and the container is placed in a reactor and reacted at 180°C for 24 hours to prepare the nanowires.
[0062] (2) Add 0.025 g of MnCl2·4H2O to the solution in step (1) and stir at room temperature for 12 h; the ratio of manganese ions in the system to calcium ions in hydroxyapatite is 1:10.
[0063] (3) After the reaction is complete, centrifuge with ultrapure water for 3 times to obtain a light brown precipitate product. Place the light brown precipitate in a refrigerator and freeze it for more than 6 hours. Use a freeze dryer to freeze-dry for 24 hours to obtain Mn-HAP nanowires.
[0064] Example 3 Preparation method of hydroxyapatite nanowires coated with an iron-rich amorphous layer: (1) 0.125 g of HAP nanowires were placed in a glycine-sodium hydroxide buffer solution with a pH of 5, stirred at room temperature overnight, and ultrasonically dispersed at a power of 600 W for 30 min to obtain a 2.5 g / L milky white suspension solution; the hydroxyapatite nanowires used were hydroxyapatite nanowires with a diameter mainly dispersed in the range of 10-50 nm and a length of about 100 µm.
[0065] The preparation method of hydroxyapatite nanowires is as follows: hydroxyapatite nanowires are prepared by a solvothermal method, firstly, sodium hydroxide, calcium chloride, sodium dihydrogen phosphate solution and a mixed solution of oleic acid, water and anhydrous ethanol are prepared respectively; then, the sodium hydroxide solution is added to the oleic acid mixed solution by a peristaltic pump, and the mixture is reacted at a speed of 700-1100 rpm for half an hour, and then the calcium chloride solution and the sodium dihydrogen phosphate solution are added respectively, with an addition interval of half an hour; finally, the mixture is poured into a polytetrafluoroethylene container, and the container is placed in a reactor and reacted at 180°C for 24 hours to prepare the nanowires.
[0066] (2) Add 0.0135 g of FeCl3·6H2O to the solution in step (1) and stir at room temperature for 3 h. The concentration of iron ions in the solution is 0.0001 M.
[0067] (3) After the reaction is complete, the mixture is centrifuged three times with ultrapure water to obtain a light yellow precipitate product. The light yellow precipitate is placed in a refrigerator and frozen for more than 6 hours. It is then freeze-dried in a freeze dryer for 24 hours to obtain Fe-HAP nanowires.
[0068] Example 4 Preparation method of hydroxyapatite nanowires coated with a copper-rich amorphous layer: (1) 0.125 g of HAP nanowires were placed in a glycine-sodium hydroxide buffer solution with a pH of 9, stirred at room temperature overnight, and ultrasonically dispersed at a power of 600 W for 30 min to obtain a 2.5 g / L milky white suspension solution; the hydroxyapatite nanowires used were hydroxyapatite nanowires with a diameter mainly dispersed in the range of 10-50 nm and a length of about 100 µm.
[0069] The preparation method of hydroxyapatite nanowires is as follows: hydroxyapatite nanowires are prepared by a solvothermal method, firstly, sodium hydroxide, calcium chloride, sodium dihydrogen phosphate solution and a mixed solution of oleic acid, water and anhydrous ethanol are prepared respectively; then, the sodium hydroxide solution is added to the oleic acid mixed solution by a peristaltic pump, and the mixture is reacted at a speed of 700-1100 rpm for half an hour, and then the calcium chloride solution and the sodium dihydrogen phosphate solution are added respectively, with an addition interval of half an hour; finally, the mixture is poured into a polytetrafluoroethylene container, and the container is placed in a reactor and reacted at 180°C for 24 hours to prepare the nanowires.
[0070] (2) Add 0.021 g of CuCl2·2H2O to the solution in step (1) and stir at room temperature for 24 h; the ratio of copper ions in the system to calcium ions in hydroxyapatite is 1:10.
[0071] (3) After the reaction is complete, centrifuge with ultrapure water for 3 times to obtain a light blue precipitate product. Put the light blue precipitate into a refrigerator and freeze it for more than 6 hours. Then use a freeze dryer to freeze-dry for 24 hours to obtain Cu-HAP nanowires.
[0072] Example 5 Preparation method of hydroxyapatite nanowires coated with zinc-rich amorphous layer: (1) 0.125 g of HAP nanowires were placed in a glycine-sodium hydroxide buffer solution with a pH of 7, stirred at room temperature overnight, and ultrasonically dispersed at a power of 600 W for 30 min to obtain a 2.5 g / L milky white suspension solution; the hydroxyapatite nanowires used were hydroxyapatite nanowires with a diameter mainly dispersed in the range of 10-50 nm and a length of about 100 µm.
[0073] The preparation method of hydroxyapatite nanowires is as follows: hydroxyapatite nanowires are prepared by a solvothermal method, firstly, sodium hydroxide, calcium chloride, sodium dihydrogen phosphate solution and a mixed solution of oleic acid, water and anhydrous ethanol are prepared respectively; then, the sodium hydroxide solution is added to the oleic acid mixed solution by a peristaltic pump, and the mixture is reacted at a speed of 700-1100 rpm for half an hour, and then the calcium chloride solution and the sodium dihydrogen phosphate solution are added respectively, with an addition interval of half an hour; finally, the mixture is poured into a polytetrafluoroethylene container, and the container is placed in a reactor and reacted at 180°C for 24 hours to prepare the nanowires.
[0074] (2) Add 0.1788 g ZnSO4·7H2O to the solution in step (1) and stir at room temperature for 3 h; the ratio of zinc ions in the system to calcium ions in hydroxyapatite is 1:2.
[0075] (3) After the reaction is complete, the mixture is centrifuged three times with ultrapure water to obtain a white precipitate product. The white precipitate is placed in a refrigerator and frozen for more than 6 hours. It is then freeze-dried in a freeze dryer for 24 hours to obtain Zn-HAP nanowires.
[0076] Comparative Example 1 The difference between Comparative Example 1 and Example 2 is that NaOH is used to adjust the pH to 9, and the other conditions are the same as those in Example 2.
[0077] Comparative Example 2 The difference between Comparative Example 2 and Example 2 is that the pH is 7, and the other conditions are the same as those in Example 2.
[0078] Comparative Example 3 The difference between Comparative Example 3 and Example 2 is that the manganese ion content in the system is increased so that the ratio of manganese ions in the system to calcium ions in hydroxyapatite is 1:1, and the other conditions are the same as those in Example 2.
[0079] 2. Test Method 1. Morphology test: (1) Ultrahigh Resolution Field Emission Scanning Electron Microscope (SEM), working principle: use electron beam to irradiate the sample surface, and obtain the magnified image of the microscopic morphology through the secondary electrons, backscattered electrons and other signals generated by the interaction between electrons and samples; model: Hitachi Regulus 8230; test conditions: the sample to be tested is glued to the sample stage with conductive glue and metal platinum particles are sputtered for 40-80 s according to the conductivity of the sample, and the acceleration voltage is 5 kV.
[0080] (2) Field emission transmission electron microscope (TEM) Working principle: The accelerated and focused electron beam is projected onto a very thin sample. The electrons collide with the atoms in the sample and change direction, thus generating a three-dimensional angle scattering. The size of the scattering angle is related to the density and thickness of the sample, so different images of light and dark can be formed; Model: JEM-F200; Test conditions: The powder sample to be tested is diluted with alcohol, ultrasonically dispersed, and then dripped onto the ultra-thin carbon film copper mesh. After the alcohol on the copper mesh evaporates, it can be used for testing.
[0081] 2. Crystal structure test: X-ray diffraction (XRD), working principle: when a beam of X-rays is incident on the crystal, the X-rays scattered by different atoms interfere with each other, and strong X-ray diffraction occurs in certain special directions; model: D8 Advance from Bruker, Germany; test conditions: X-ray target is Cu palladium, Kα line wavelength is λ=0.15406nm; test angle is 10-80°; test voltage V=40 kV, current I=40 mA.
[0082] 3. Material chemical properties and composition test: Working principle: Use X-rays, such as Al Ka = 1486.6eV, to interact with the sample surface, use the photoelectric effect to stimulate the sample surface to emit photoelectrons, use the energy analyzer to measure the photoelectron kinetic energy (KE), and then get the binding energy (BE) of the excited electrons according to BE=hv-KE-WF; Model: ESCALAB 250Xi.
[0083] 4. Thermal stability test: Simultaneous Thermal Analyzer (TG / DSC), working principle: TG: The principle of thermogravimetric method is to study the relationship between the mass of the test substance and temperature (or time) under program temperature control. By analyzing the thermogravimetric curve, it can be known at what temperature the test substance changes, and based on the weight loss, the lost mass can be calculated. Through the first differential curve of mass and temperature, the speed of mass change of the test substance can be analyzed.
[0084] III. Analysis of test results of various embodiments and comparative examples (1) Figure 1 TEM image of the hydroxyapatite (Al-HAP) nanowires coated with an aluminum-rich amorphous layer in Example 1. It can be seen from the image that the hydroxyapatite nanowires prepared by the method in Example 1 are coated with an amorphous coating. Figure 5 and Fig. 9 TEM images of Mn-HAP nanowires and Fe-HAP nanowires, respectively. It can be seen from the images that the hydroxyapatite nanowires prepared by the methods in Example 2 and Example 3 are coated with an amorphous coating.
[0085] In Comparative Example 1, alkali solution was used to directly adjust the pH value, and the prepared Mn-HAP nanowires were as follows: Fig.14 As shown, no amorphous layer was found, indicating that the amorphous layer can only be generated by using a buffer solution to ensure that the pH remains stable during the reaction.
[0086] In Comparative Example 2, the pH value was adjusted to 7 using a buffer solution, and the prepared Mn-HAP nanowires were as follows: Fig.15 As shown, no amorphous layer was found, indicating that pH 9 is more suitable for preparing Mn-HAP nanowires.
[0087] In Comparative Example 3, the manganese ion content in the system was increased to be the same as the calcium ion content in the solution. Through transmission electron microscopy, small particles such as Fig.16 The reason is that the manganese ion concentration is too high to form an amorphous layer, and small crystalline particles are generated.
[0088] (2) Figure 2 Figure 2 is the XRD pattern of Al-HAP nanowires and pure hydroxyapatite (HAP) nanowires in Example 1. By comparing with the XRD patterns of pure hydroxyapatite nanowires and nanowires calcined at 900°C, the position and intensity of the crystallization peak of Al-HAP are similar to those of pure hydroxyapatite nanowires, while the aluminum-rich nanowires calcined at 900°C have a new crystallization peak, which is the Ca9Al(PO4)7 crystal phase, and the intensity of the crystallization peak is significantly improved. This is because the outer amorphous layer of the nanowire is converted into a crystalline phase at 900°C. Figure 6 , Fig.10 They are TEM images of Mn-HAP, HAP, Mn-HAP-900°C and Fe-HAP, HAP, Fe-HAP-900°C nanowires, respectively. It can be seen from the figures that the hydroxyapatite nanowires prepared by the methods in Example 2 and Example 3 are coated with the corresponding amorphous coatings.
[0089] (3) Figure 3 The XPS graphs of Al-HAP nanowires and HAP nanowires in Example 1 show that pure HAP nanowires contain three elements: Ca, P, and O. Compared with pure HAP, the XPS graph of Al-HAP nanowires contains more Al elements, indicating that Al is involved in the ion exchange of HAP nanowires. 3+ Successfully introduced into nanowires. Figure 7 The XPS test images of Mn-HAP and HAP nanowires are shown in Figure 2. Fig.11 The XPS test images of Fe-HAP and HAP nanowires show that Mn 2+ , Fe 3+ are introduced into the nanowires respectively.
[0090] (4) Figure 4 , Figure 8 and Fig.12 These are the SEM images of Al-HAP, Mn-HAP, and Fe-HAP nanowires at a magnification of 10,000 times. It can be seen that the Al-HAP, Mn-HAP, and Fe-HAP nanowires still maintain the morphology of nanowires and have a very high aspect ratio. Coating the amorphous layer on the periphery of the nanowires does not destroy the original structure of the nanowires.
[0091] (5) Fig.13 This is the thermogravimetric analysis diagram of Al-HAP in Example 1. It can be concluded that the decomposition temperature of Al-HAP is 824°C, while the decomposition temperature of pure HAP is 701°C, indicating that the thermal stability is greatly improved.
[0092] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A hydroxyapatite nanowire coated with a metal ion-rich amorphous layer, characterized in that: The invention comprises hydroxyapatite nanowires and a metal ion-rich amorphous layer coated on the surface thereof, wherein the aspect ratio of the hydroxyapatite nanowires is 500-10000, and the ratio of the diameter of the hydroxyapatite nanowires to the thickness of the metal ion-rich amorphous layer is (5-50):
1.
2. The hydroxyapatite nanowire coated with a metal ion-rich amorphous layer according to claim 1, characterized in that: The diameter of the hydroxyapatite nanowire is 10-100 nm, and the length is 100-500 μm; the thickness of the metal ion-rich amorphous layer is 1-5 nm.
3. The hydroxyapatite nanowire coated with a metal ion-rich amorphous layer according to claim 1, characterized in that: The metal ions include one of iron, aluminum, copper, manganese and zinc.
4. The method for preparing hydroxyapatite nanowires coated with a metal ion-rich amorphous layer according to any one of claims 1 to 3, characterized in that: The steps include: S1, dispersing hydroxyapatite nanowires in a buffer solution to obtain a hydroxyapatite nanowire suspension solution; S2, adding a soluble metal salt to the hydroxyapatite nanowire suspension solution, stirring for reaction, and washing, centrifuging, and freeze-drying after the reaction is completed to obtain hydroxyapatite nanowires coated with a metal ion-rich amorphous layer.
5. The method for preparing hydroxyapatite nanowires coated with a metal ion-rich amorphous layer according to claim 4, characterized in that: The buffer solution is an ammonium formate-formic acid buffer solution or a glycine-sodium hydroxide buffer solution, and the pH of the buffer solution is 5.0-9.
0.
6. The method for preparing hydroxyapatite nanowires coated with a metal ion-rich amorphous layer according to claim 4, characterized in that: The concentration of the hydroxyapatite nanowires in the hydroxyapatite nanowire suspension solution is 2-5 g / L.
7. The method for preparing hydroxyapatite nanowires coated with a metal ion-rich amorphous layer according to claim 4, characterized in that: The dispersion step in step S1 includes placing the hydroxyapatite nanowires in a buffer solution, stirring at room temperature for 12 to 24 hours, and then performing ultrasonic dispersion at a power of 600 to 800 W for 30 to 60 minutes.
8. The method for preparing hydroxyapatite nanowires coated with a metal ion-rich amorphous layer according to claim 4, characterized in that: The metal ion concentration in step S2 is 0.0001-0.025 mol / L, and the molar ratio of the metal ion to Ca2+ in hydroxyapatite is 1:(2-10).
9. The method for preparing hydroxyapatite nanowires coated with a metal ion-rich amorphous layer according to claim 3, characterized in that: The stirring conditions in step S2 are: stirring at room temperature for 3 to 24 hours, and a stirring speed of 400 to 800 rpm.
10. A tooth enamel repair material, characterized in that: The method is prepared from the hydroxyapatite nanowires coated with a metal ion-rich amorphous layer according to any one of claims 1 to 3.
Citation Information
Patent Citations
Hydroxy apatite / zirconia composite bio-ceramic and preparation method thereof
CN104399116A
Calcium-deficient aluminum-doped hydroxyapatite powder, preparation method thereof and application
CN107161973A
Super-hydrophobic coating based on enamel bionic structured hydroxyapatite nanowire assemblies
CN107418278A
Method for doping of metal ions in hydroxyapatite nano crystal
CN107585751A
Preparation method and application of ion-codoped transparent hydroxyapatite ceramic
CN111467566A